Discriminative stimulus properties of the typical antipsychotic haloperidol compared to other antipsychotic drugs in C57BL/6 mice. Issue 6 (September 2019) - Donahue, Timothy J.; Webster, Kevin A.; Hillhouse, Todd M.; De Oliveira, Eliseu O.; Porter, Joseph H.
Abstract : Haloperidol (HAL) was developed in 1958 for the treatment of schizophrenia and is classified as a typical antipsychotic drug (APD). Effective in treating positive symptoms of schizophrenia, it does not treat negative symptoms and produces extrapyramidal motor side-effects. Atypical APDs like clozapine treat both positive and negative symptoms of schizophrenia, have reduced extrapyramidal motor side-effects and possess other clinical advantages. This study used a drug discrimination assay to allow a direct comparison between the subjective effects of HAL and other APDs. Eleven C57BL/6 mice were trained to discriminate 0.05 mg/kg HAL from the vehicle in a two-lever drug discrimination task. The HAL generalization curve (0.001563–0.2 mg/kg) yielded an ED50 =0.0024 mg/kg (95% confidence interval: 0.0012–0.0048 mg/kg). The typical APD chlorpromazine produced full substitution at 4.0 mg/kg with 82.7% drug-lever responding (%DLR) with significant rate suppression and partial substitution (73.9% DLR) at 1.0 mg/kg with no rate suppression. The atypical APD clozapine produced partial substitution at 2.5 mg/kg (64.8% DLR) with significant rate suppression. The atypical APD amisulpride failed to substitute for HAL with a maximum %DLR of 57.9% at 40 mg/kg with no rate suppression. The atypical APD aripiprazole partially substituted with a maximum of 75.9% DLR at 1.25 mg/kg with significant rate suppression. These results demonstrate that HAL can be trained as a discriminative stimulus in C57BL/6 mice, and its discriminative cue appears to be unique and distinct from that of atypical APDs.